2019
DOI: 10.1093/brain/awz319
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microglial Wnt/β-catenin signalling drives microglial pro-inflammatory activation in the developing brain

Abstract: Inflammatory activation of microglia in the brains of prematurely born infants can lead to permanent neurological sequelae. Van Steenwinckel et al. show that a reduction in microglial Wnt signalling is necessary and sufficient to drive a microglial phenotype causing hypomyelination, and establish the Wnt pathway as a viable therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 109 publications
(189 citation statements)
references
References 117 publications
(176 reference statements)
13
174
2
Order By: Relevance
“…For example, studies in vitro have shown that Wnt3a and Wnt5a can counteract LPS-induced microglia activation [75]. In contrast, in preterm-born infants and in different postnatal animal models of injured-induced neuroinflammation, downregulation of the expression of Wnt signaling components seems a prerequisite for pro-inflammatory activation of microglia [76]. SFRP1 upregulation could lead to the same net effect, inducing at least the down-regulation of the expression of Axin2 or Lef1, genes that targets and read-out of Wnt/βcatenin pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in vitro have shown that Wnt3a and Wnt5a can counteract LPS-induced microglia activation [75]. In contrast, in preterm-born infants and in different postnatal animal models of injured-induced neuroinflammation, downregulation of the expression of Wnt signaling components seems a prerequisite for pro-inflammatory activation of microglia [76]. SFRP1 upregulation could lead to the same net effect, inducing at least the down-regulation of the expression of Axin2 or Lef1, genes that targets and read-out of Wnt/βcatenin pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in cultured mouse microglial cells that express the Fzd4/5/7/8 receptors as well as LRP5/6, Wnt3a stimulation activated β-catenin signaling, increasing the expression of pro-inflammatory mediators such as IL6, IL12, and TNFα (Halleskog et al, 2011). However, recent findings have demonstrated that deactivation of the β-catenin signaling induced a pro-inflammatory phenotype in microglial cells (Van Steenwinckel et al, 2019). Interestingly, delivery into the brain of a Wnt agonist that mediates canonical pathway activation specifically in microglia by using a microglia-specific targeting nano-carrier, microglial cell pro-inflammatory phenotype was attenuated (Van Steenwinckel et al, 2019).…”
Section: Implication In Immunitymentioning
confidence: 97%
“…However, recent findings have demonstrated that deactivation of the β-catenin signaling induced a pro-inflammatory phenotype in microglial cells (Van Steenwinckel et al, 2019). Interestingly, delivery into the brain of a Wnt agonist that mediates canonical pathway activation specifically in microglia by using a microglia-specific targeting nano-carrier, microglial cell pro-inflammatory phenotype was attenuated (Van Steenwinckel et al, 2019). More investigations are required to clearly address the complex role of Wnt pathway in regulating microglial cell activation.…”
Section: Implication In Immunitymentioning
confidence: 99%
“…Microglial activation is almost ubiquitously reported across forms of perinatal brain injury, and a causal role for these processes in injury has been demonstrated across paradigms (117,118). Conversely, a neuroprotective role for microglia is also shown in other experimental settings (119,120).…”
Section: Reactive Gliosismentioning
confidence: 99%